Global Commodity Prices, Monetary Transmission, and Exchange Rate Pass-Through in the Pacific Islands - Peiris, Shanaka; Ding, Ding. (Washington, D.C. : International Monetary Fund, 2012)
Pacific Islands countries are vulnerable to commodity price shocks, and this poses challenges to monetary policy. The high degree of exchange rate pass-through to headline inflation and the weak monetary transmission mechanism in PICs suggest a greater efficacy of exchange rate changes in affecting inflation rather than monetary policy. To assess the tradeoff between the use of the exchange rate and monetary policy in macroeconomic stabilization, we employ a model-based approach to examine the optimal policy in response to the historical distribution of exogenous shocks in a Pacific Island (Tonga). The empirical evidence and model simulations tilt in the favor of exchange rate policy given the close relationship between exchange rate changes and headline inflation and the low interest rate sensitivity of aggregate demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet